Project-based dance learning in Inclusive Dance Education in junior high schools: A Scoping Review - Kholifah, Zahrah Luthfi; Rita Milyartini; Juju Masunah (Journal of Practice Learning and Educational Development, 2026)
Inclusive dance education aims to provide equal learning experiences for all students, including those with special needs. Project-based learning is a relevant approach because it emphasizes active engagement, collaboration, and creative processes that can be adapted to students' varying abilities. However, literature reviews that specifically discuss the implementation of this approach in the context of inclusive dance education are still limited. This scoping review aims to map empirical evidence on implementation strategies, pedagogical benefits, and challenges in implementing project-based dance learning in inclusive secondary schools. Literature searches were conducted through the Scopus, Springer, and Google Scholar databases for publications from 2021 to 2025. The findings show that project-based learning can improve movement creativity, collaborative skills, self-confidence, and social participation of students with special needs. The application of this model has also been proven to encourage positive interactions between students and strengthen character traits such as responsibility and independence. However, a number of obstacles were encountered, including limited facilities, the need to adapt instructions and communication for students with disabilities, and the low level of preparedness among teachers in designing truly inclusive dance projects. This study provides a conceptual and practical foundation for educators, policymakers, and researchers to develop project-based dance learning designs that are more responsive to the diversity of students' abilities.